TRAINING ON THE PREPARATION OF ANNUAL WORK PLANS AT ABDOEL WAHAB SJAHRANIE HOSPITAL (Jurnal Abdimas Administrasi Kesehatan, 2023)
Before the daily project work takes place Abdoel Wahab Sjahranie hospital, the annual works plans needs to be clarified. The responsibilities and accountabilities need to be documented. The preparation of annual work plan is responsible for the management. However, the questions such as to whom he should report to and if there is a need for a project assurance body, need to be explicated as well. A common project organization comprises project sponsor, project board, project manager and project team. Subjected to the complexity of the project, the project assurance body such as quality manager or quality auditor might also be added to the project organization. â€œTraining and development are term is referring to planned efforts designed facilitate the acquisition of relevant skills, knowledge and attitudes by organizations members. Development focuses more on improving the decision making and human relations skills and the presentation of a more factual and narrow subject matterâ€. The community service method is in the form of training on the preparation of an annual work plan at the Abdoel Wahab Sjahranie Regional Hospital as many as 60 people. The assistance of health administration participants is expected to increase knowledge about training on the preparation of annual work plans at the Abdoel Wahab Sjahranie Regional Hospital
Keywords: Preparation of annual work plans